INTERNAL CONTROL IN CASH CONTROL DURING THE NEW NORMAL AT BPRS AL WASLIYAH MEDAN - Siti Mujiatun; Afif Badawi; Windy Anggrainy Siregar; Rahmayati Rahmayati (Proceeding International Seminar of Islamic Studies, 2022)
The aim is for internal control in cash control during the new normal period at BPRS Al Wasliyah in accordance with the components of internal control (internal control) in the new normal era which is carried out strictly. according to the theory of the Committee of Sponsoring Organizations (COSO). The problem studied in this study is whether the role of internal control in cash control with internal control components is in accordance with the theory of the Committee of Sponsoring Organizations (COSO). This research is a source triangulation test with a qualitative descriptive approach. The research subjects were employees of BPRS AL WASHLIYAH Medan . The data collection technique used was a focused interview where the researcher asked the informants regarding things that had been prepared beforehand. Analysis of the data used is by using data obtained from interviews, observation and documentation, by collecting, describing, and forming it in a pattern. The results obtained by Internal control in cash control during the new normal period at BPRS Al Wasliyah Medan are in accordance with the components of internal control according to COSO theory, which components are the control environment, risk assessment, control, information and communication activities and monitoringKeywords: Internal Control, New Normal, Cash Control